2005
DOI: 10.1021/ja0468123
|View full text |Cite
|
Sign up to set email alerts
|

Single-Chain Magnet (NEt4)[Mn2(5-MeOsalen)2Fe(CN)6] Made of MnIII−FeIII−MnIII Trinuclear Single-Molecule Magnet with an ST = 9/2 Spin Ground State

Abstract: The cyano-bridged trinuclear compound, (NEt(4))[Mn(2)(salmen)(2)(MeOH)(2)Fe(CN)(6)] (1) (salmen(2)(-) = rac-N,N'-(1-methylethylene)bis(salicylideneiminate)), reported previously by Miyasaka et al. (ref 19d) has been reinvestigated using combined ac and dc susceptibility measurements. The strong frequency dependence of the ac susceptibility and the slow relaxation of the magnetization show that 1 behaves as a single-molecule magnet with an S(T) = (9)/(2) spin ground state. Its relaxation time (tau) follows an A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
205
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(220 citation statements)
references
References 93 publications
12
205
1
2
Order By: Relevance
“…In addition, unlike the reported in ref. 48 assembly by means of a mutual bridging of the {Mn(5TMAMsalen)} units by phenolate oxygen atoms similar to in ref [47] and forming the 7(CN)-W-CN-Mn(-O-)2-Mn-NC-W(CN)7 core. However, in such a case the valence stretches of CN would not experience some significant shifting in higher frequencies as it take place for 2.…”
Section: Description Of Molecular Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, unlike the reported in ref. 48 assembly by means of a mutual bridging of the {Mn(5TMAMsalen)} units by phenolate oxygen atoms similar to in ref [47] and forming the 7(CN)-W-CN-Mn(-O-)2-Mn-NC-W(CN)7 core. However, in such a case the valence stretches of CN would not experience some significant shifting in higher frequencies as it take place for 2.…”
Section: Description Of Molecular Structurementioning
confidence: 99%
“…Cyano-bridged metal assemblies have provided a large number of compounds with SMM [31][32][33][34][35][36][37][38] and SCM behavior [39][40][41][42][43][44][45][46][47][48]. The greater part of these materials comprises 3d metal ions as the core magnetic units.…”
Section: Introductionmentioning
confidence: 99%
“…®ÇAEÎÇÐÐÂâ ÓÇÎÂÍÔÂÙËâ ÐÂÏÂÅÐËÚÇÐÐÑÔÕË ÐÂÃÎáAEÂ-ÇÕÔâ Ä ×ÇÓÓÑÏÂÅÐËÕÐÞØ ( ¶®) [20,22], ×ÇÓÓËÏÂÅÐËÕÐÞØ [19],  ÕÂÍÉÇ ÐÇÍÑÎÎËÐÇÂÓÐÞØ ÂÐÕË×ÇÓÓÑÏÂÅÐËÕÐÞØ [21] ËÊËÐÅÑÄÔÍËØ ÙÇÒÑÚÍÂØ. £ ÑÕÔÖÕÔÕÄËÇ ÐÇÍÑÎÎËÐÇÂÓÐÑÌ ÔÕÓÖÍÕÖÓÞ ÓÇÎÂÍÔÂÙËâ Ä ¡ ¶®-ÙÇÒÑÚÍÂØ ÕÂÍÉÇ ÄÑÊ-ÏÑÉÐÂ, ÇÔÎË ÙÇÒÑÚÍ ÔÑAEÇÓÉËÕ ÐÇÚÈÕÐÑÇ ÍÑÎËÚÇÔÕÄÑ ÔÒË-ÐÑÄ [23].…”
Section: £äçAeçðëçunclassified
“…1,9,11 The magnetic properties of such 1D systems were theoretically predicted by Glauber in the 1960s: 12 At low temperature, the magnetization relaxes slowly with a relaxation time that follows an Arrhenius law s ¼ s 0 Áexp(D/k B T), and no phase transition to threedimensional (3D) magnetic long-range order occurs before the magnetization blockage. 10,13 Subsequently, several other compounds were shown to exhibit SCM behavior, 11,[14][15][16][17][18][19][20][21] with quantum effects influencing the magnetization dynamics at low temperatures. 22 In particular, several works [23][24][25] showed that the requirements necessary to observe Glauber dynamics-a strong Ising-like anisotropy and a very low ratio of interchain/intrachain magnetic exchange interactions-are fulfilled in [Dy(hfac) 3 {NIT(C 6 H 4 OPh)}] (in short DyPhOPh).…”
Section: Introductionmentioning
confidence: 99%